Amoebicidal compounds from medicinal plants. - Di Stasi, L. C. (My University, 1995)
A series of the natural constituents with amoebicidal activity isolated from several medicinal plants is shown. A list of the medicinal plants potentially active as amoebicide and/or against dysentery also is demonstrated. The present data grouping of the natural compounds and medicinal plants can be an important source of information for the selection of research plant material by the investigators interested in the discovery of new biologically active compounds as amoebicide.
Keywords: antiamebic agent; animal; Brazil; chemical structure; chemistry; classification; drug effect; dysentery; Entamoeba histolytica; human; isolation and purification; medicinal plant; phytotherapy; review; synthesis; Amebicides; Animals; Dysentery, Amebic; Humans; Molecular Structure; Phytotherapy; Plants, Medicinal